Is reproductive strategy a key factor in understanding the evolutionary history of Southern Ocean Asteroidea (Echinodermata)?. Issue 15 (16th July 2019) - Moreau, Camille; Danis, Bruno; Jossart, Quentin; Eléaume, Marc; Sands, Chester; Achaz, Guillaume; Agüera, Antonio; Saucède, Thomas
Abstract: Life traits such as reproductive strategy can be determining factors of species evolutionary history and explain the resulting diversity patterns. This can be investigated using phylogeographic analyses of genetic units. In this work, the genetic structure of five asteroid genera with contrasting reproductive strategies (brooding: Diplasterias, Notasterias and Lysasterias versus broadcasting: Psilaster and Bathybiaster ) was investigated in the Southern Ocean. Over 1, 400 mtDNA cytochrome C oxidase subunit I (COI) sequences were analysed using five species delineation methods (ABGD, ASAP, mPTP, sGMYC and mGMYC), two phylogenetic reconstructions (ML and BA), and molecular clock calibrations, in order to examine the weight of reproductive strategy in the observed differences among phylogeographic patterns. We hypothesised that brooding species would show higher levels of genetic diversity and species richness along with a clearer geographic structuring than broadcasting species. In contrast, genetic diversity and species richness were not found to be significantly different between brooders and broadcasters, but broadcasters are less spatially structured than brooders supporting our initial hypothesis and suggesting more complex evolutionary histories associated to this reproductive strategy. Broadcasters' phylogeography can be explained by different scenarios including deep‐sea colonisation routes, bipolarity or cosmopolitanism, and sub‐Antarctic emergence for the genus Bathybiaster ; Antarctic‐ New Zealand faunal exchanges across the Polar Front for the genus Psilaster . Brooders' phylogeography could support the previously formulated hypothesis of a past trans‐Antarctic seaway established between the Ross and the Weddell seas during the Plio‐Pleistocene. Our results also show, for the first time, that the Weddell Sea is populated by a mixed asteroid fauna originating from both the East and West Antarctic. Abstract : The asteroid genetic structure of five genera with contrasted reproductive strategies (brooding versus broadcasting) was investigated in the Southern Ocean. We hypothesise that brooding species will show higher genetic diversity and greater species richness with a more pronounced genetic structuring in space, compared to broadcasting species. We found that reproductive strategy does not affect genetic diversity nor species richness of Southern Ocean asteroids but played a key role in the spatial patterns of asteroid diversification in the Southern Ocean.